2003
DOI: 10.1074/jbc.m207546200
|View full text |Cite
|
Sign up to set email alerts
|

The Growth Hormone-binding Protein Is a Location-dependent Cytokine Receptor Transcriptional Enhancer

Abstract: In the rat, a growth hormone-binding protein (GHBP) exists that is derived from the growth hormone (GH) receptor gene by an alternative mRNA splicing mechanism such that the transmembrane and intracellular domains of the GH receptor are replaced by a hydrophilic carboxyl terminus. In isolation, the GHBP is inactive, although it does compete with the receptor for ligand binding in the extracellular space and therefore inhibits the cellular response to GH. The GHBP is also located intracellularly and is transloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 65 publications
0
17
0
Order By: Relevance
“…(72) In the context of nuclear translocation as it relates to signal transduction, several studies have shown in rat cell lines that all three molecules, GH, GHR and GHBP (the splice variant forms), are translocated to the nucleus. (73)(74)(75)(76) Both GHR and GHBP require GH stimulation to translocate to the nucleus. Further, nuclear rat GHBP appears to act as a transcriptional inducer of STAT5.…”
Section: Prolactin and Growth Hormonementioning
confidence: 99%
“…(72) In the context of nuclear translocation as it relates to signal transduction, several studies have shown in rat cell lines that all three molecules, GH, GHR and GHBP (the splice variant forms), are translocated to the nucleus. (73)(74)(75)(76) Both GHR and GHBP require GH stimulation to translocate to the nucleus. Further, nuclear rat GHBP appears to act as a transcriptional inducer of STAT5.…”
Section: Prolactin and Growth Hormonementioning
confidence: 99%
“…Thus, nuclear accumulation of Prl receptors as well as their overexpression in intrahepatically transplanted RS1 cholangiocarcinoma cells and in hepatocytes of tumor bearing animals can serve as a specific marker of cholangiocarcinoma. Since we have used monoclonal antibodies U5 to the extracellular domain of rat Prl receptor, it was revealed that nuclear accumulation may be due to both full length Prl receptor or Prl binding protein as have been found for GH binding protein [9,172] . Appearance of Prl receptors in the nucleus is associated with Prl participation in the regulation of the proliferation process.…”
Section: Developmentmentioning
confidence: 99%
“…Rat growth hormone binding protein (GHBP) that is a product of alternative splicing of GH receptor gene with an intact extracellular domain and without transmembrane and intracellular domains replaced by short carboxyterminal sequences, is also localized in cell nuclei in in vitro and in vivo experiments upon GH stimulation. Nuclear localized GHBP acts as a potent enhancer of STAT5 mediated transcription presumably by binding to PIAS proteins and thereby enhances the action of both GH and other members of the cytokine receptor superfamily [9,172] .…”
Section: Developmentmentioning
confidence: 99%
“…Importantly, the internalisation and nuclear uptake of GH was not observed in the absence of an intact GHR. Graichen et al have reported that GH and GHR co-translocate to the nucleus and receptor phosphorylation may be the stimulus for nuclear translocation (Graichen et al, 2003).…”
Section: Nuclear Localisationmentioning
confidence: 99%
“…Analysis of a number of clinical cancer samples has shown GHR localised to the nucleus, including B-cell lymphomas, mammary carcinoma, melanoma and prostate tumours (Lincoln et al, 1998;Mertani et al, 1996). The GHBP, and by implication the nuclear GHR, has been shown to act as a transcription factor capable of direct transactivation in a mammalian β-galactosidase reporter assay (Graichen et al, 2003;Conway-Campbell et al, 2008).…”
Section: Nuclear Localisationmentioning
confidence: 99%